Patrón de asentamiento tardío y ecología cultural del alto Qaracha - Taquiri González, Marco (2021)
This article shows the results of the late pre-Hispanic settlement of the upper Qaracha basin in the dissected plateau of the central region of Ayacucho (3000 – 4000 meters above sea level). The archaeological record made it possible to evaluate the extension and diversity of the high Andean territorial occupation at a local scale and its relationship with the ecological environment. The late settlement of this territory was concentrated in large villages that generally have a central habitable nucleus with stone architecture. The habitable nucleus present homogeneous patterns of construction technology and spatial design of large housing complexes with corrals, terraces and funeral structures. The territorial function of the villages is discussed and it is proposed that this type of settlements constitute tangible evidence to characterize a model of village life and pre-Hispanic territorial dynamics at a local scale, in a period of latent conflict.